Vehicular Ad-Hoc Networks for Smart Cities Second International Workshop, 2016 - Laouiti, Anis.; Qayyum, Amir.; Mohamad Saad, Mohamad Naufal; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents selected articles from the Second International Workshop on Vehicular Adhoc Networks for Smart Cities, 2016 (IWVSC'2016). In order to promote further research activities and challenges, it highlights recent developments in vehicular networking technologies and their role in future smart cities.
Vehicle-to-vehicle (V2V) communications -- Vehicle-to-infrastructure (V2I) communications for smart cities -- Medium access control protocols for VANETs -- Routing protocols for active safety in VANETs -- Geographical routing protocols for VANETs -- Architectures, algorithms and protocols design for data dissemination, processing, and aggregation in vehicular networks -- Security, privacy in vehicular networks -- QoS provisioning for vehicular networks -- Vehicular clouds: architecture design, algorithms and protocols for smart cities -- Software defined networking and virtualization for vehicles -- Vehicular social networks -- Group mobility/Platooning/Autonomous driving in smart cities -- 5G technologies for vehicular communications -- Simulation and performance evaluation techniques for vehicular networks -- Results from experimental systems and testbeds for VANET.
Keywords: Computational intelligence; Transportation engineering; Traffic engineering; Telecommunication; Computer input-output equipment; Automotive engineering; Computational Intelligence; Transportation Technology and Traffic Engineering; Communications Engineering, Networks; Input/Output and Data Communications; Automotive Engineering